Why Do Indonesia Zakat Collection Not as Effective as Malaysia's? - Aris Puji Purwatiningsih (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2020)
The purpose of this article is to find out how the practices and problems of zakat in Indonesia are not yet optimal such as Malaysia. The findings show that the main problems faced in managing zakat in Indonesia are: first, there is no government regulation that requires zakat to all Muslim citizens who have reached Nisab. Secondly, the Moslem community prefers to pay zakat to known people rather than to existing formal zakat institutions. Third, the lack of optimal cooperation between zakat institutions owned by the government and private parties. The writing method used is descriptive research sourced from previous articles about zakat especially zakat management in Indonesia and Malaysia. The findings of this study are expected to be input for all parties involved in zakat management to be more optimal.